The Canadian Commonwealth - Laut, Agnes C., 1871-1936 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Canadian Commonwealth" by Agnes C. Laut is a historical account written in the early 20th century. The book focuses on the formation and development of Canadian national consciousness, exploring Canada's unique path to identity and unity compared to other nations, particularly in the context of its diverse cultural roots and political landscape. It discusses the colonial legacies, the impact of immigration, and the tensions between various regional identities, notably among French and English Canadians. The opening portion of the work delves into the concept of national consciousness in Canada, contrasting its development with that of other nations. Laut emphasizes that Canada's identity was forged not through conquest or a desire for dominance, but through unyielding determination and collective ideals stemming from religious, political, and practical pursuits across its various groups. She charts the initial settlement of Canada, the struggles for acknowledgement and governance following the fall of New France, and the persistence of its people to create a system that values law and integrity over mere economic success. This section sets the stage for a nuanced discussion on the roles of different peoples in Canada$1 (Bs historical journey, suggesting that the nation's consciousness emerged out of challenges and ideals rather than from the chase of material wealth or territorial expansion. (This is an automatically generated summary.)s
Release date is 2006-03-21
E-text prepared by Al Haines
Keywords: Canada -- Economic conditions